Improving Teachers’ and Students’ Understanding of Solar Energy Using an Interactive PV Learning Kit - Nuha Nadhiroh; Murie Dwiyaniti; Arum Kusuma Wardhany; Nagib Muhammad; Jonatan Romulus Martius; Arjuna Muhammad Utomo; M. Wildan Mukholadun Saujana; Yuto Yamashiro (Universitas Ahmad Dahlan, 2026)
Background: Solar energy utilization holds great potential to be introduced at an early age, especially for elementary school students in island regions such as Tidung Island, which receives high solar radiation throughout the year. However, the lack of hands-on, interactive learning media and limited teacher understanding of photovoltaic (PV) technology have become major obstacles in renewable energy education. Contribution: This study proposes an interactive PV learning kit (SolarPuz-Kit) as a technology-enhanced educational intervention to enhance teachers’ and students’ competencies. It also contributes to the development of experiential learning approaches in renewable energy education. Method: This study employed a pre-experimental one-group pretest–posttest design involving elementary school students. The implementation stages include the development of a portable PV trainer kit, and hands-on learning intervention sessions. Results: The trainer kit consists of a 30 Wp solar panel and various electrical components for simulating DC energy distribution. Evaluation through pre- and post-tests revealed a significant improvement in student understanding—an 85% increase, from an average score of 36.47 to 67.64. Conclusion: The results demonstrate that the interactive SolarPuz-Kit effectively enhances renewable energy literacy and technical problem-solving skills among students. This study highlights the effectiveness of hands-on, game-based learning in supporting conceptual understanding and provides a scalable instructional strategy for renewable energy education in remote island contexts.